The power of feelings : personal meaning in psychoanalysis, gender, and culture - Chodorow, Nancy, 1944- (Yale University Press, 1999)
"In the middle of the twentieth century, leading cultural critics and visionaries - Erik Erikson, Lionel Trilling, Herbert Marcuse, and many others - turned to psychoanalysis as a measure of human personal and cultural fulfillment. Now, as we enter a new millennium, Nancy J. Chodorow, well-known feminist theorist and psychoanalyst, takes her place in this line of eminent thinkers and revitalizes their project. Psychoanalysis, she claims, offers in its clinical goals and its vision of possibility insight into the nature of subjectivity and the quality of relations with others. Psychoanalytic theory continues centuries of reflection and speculation about the good life."--Jacket